The Effect of Inquiry Learning and Discovery Learning Models on Students' Islamic Religious Education Learning Outcomes: A Comparative Study at SMAN 11 Mandau - Yurna Yanti; Risnawati Risnawati; M Fikri Hamdani (UIN Fatmawati Sukarno Bengkulu, 2025)
This research was motivated by the low learning outcomes in PAI subjects at SMAN 11 Mandau. This research aims to: 1) test the influence of inquiry learning and discovery learning models on PAI learning outcomes at Mandau State High School; 2) compare the influence of inquiry learning and discovery learning models on PAI learning outcomes at Mandau State High School. The research was carried out using quantitative research methods with a quasi-experimental design on 25 class X students. Data collection was carried out using cognitive tests. The data analysis technique uses the independent sample t test with the SPSS application. The research results are 1) the two models, namely inquiry and discovery, both have a significant influence on student PAI learning outcomes at SMAN 11 Mandau; 2) the inquiry learning model has a more significant influence compared to discovery learning on understanding concepts in PAI learning at SMAN 11 Mandau. This is based on the results of data analysis, where the value of t=-4.906 and p=0.000 <0.05, so H0 is rejected and H1 is accepted. This means there is a significant difference between the learning outcomes of students taught using the Inquiry Learning and Discovery Learning methods. Thus, to improve understanding of concepts in PAI learning, it is recommended that teachers use the inquiry model.